2021
DOI: 10.12968/bjon.2021.30.11.666
|View full text |Cite
|
Sign up to set email alerts
|

Placement of finger oximeter on the ear: comparison with oxygen saturation values taken from the finger

Abstract: Pulse oximetry is widely used to assess oxygen saturation (SpO2) in order to guide patient care and monitor the response to treatment. However, inappropriate oximeter probe placement has been shown to affect the measured oximetry values in healthy and normoxic outpatients. This study evaluated how treatment decisions might be impacted by SpO2 values obtained using a finger probe placed on the pinna of the ear in a cohort of 46 patients receiving non-invasive ventilation compared with values obtained from a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The limited literature available suggested that off-label placement could potentially give erroneous readings and negatively impact decisions about managing oxygen therapy. 10,11 No evidence supported the use of off-label placement. To evaluate the scope of the local problem, we assessed resources, the frequency of off-label use, and health care staff members' knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The limited literature available suggested that off-label placement could potentially give erroneous readings and negatively impact decisions about managing oxygen therapy. 10,11 No evidence supported the use of off-label placement. To evaluate the scope of the local problem, we assessed resources, the frequency of off-label use, and health care staff members' knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…10 Furthermore, the limited literature that exists suggests that off-label placement, such as placement of a finger-or toe-designated sensor on an earlobe, may lead to overestimation of a patient's oxygenation status. 10,11 Although 3 studies have assessed this specific practice, only 2 studies compared off-label sensor placement with the reference standard, arterial blood gas measurement. [10][11][12] These studies have limitations; neither reported using power analysis and both relied upon small sample sizes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this knowledge, clinicians continue to place finger probes on patients’ ears when readings from the finger are not feasible or appear too low. 17…”
Section: Clinical Applicationsmentioning
confidence: 99%